The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/bmjpo-2019-000578
|View full text |Cite
|
Sign up to set email alerts
|

Parental understanding of our communication of morbidity associated with paediatric cardiac surgery: a qualitative study

Abstract: BackgroundFollowing paediatric cardiac surgery, quality of life may be significantly impacted by morbidities associated with cardiac surgery. Parental understanding of the potential for postoperative morbidity is important for informed decision making. As part of a broader research study, we aimed to elicit parental understanding and experience of the communication of morbidities following their child’s cardiac surgery, using traditional focus groups together with an online forum.MethodsThe Children’s Heart Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The Children's Heart Federation, Little Hearts Matter and the Somerville Foundation, all of which are national UK charities dedicated to the support of patients with CHD and their families, facilitated and moderated one or more closed, anonymous, asynchronous online discussion groups via their Facebook pages, following an approach that we have successfully used in previous work. 19 20 We specifically chose these three charities because we wanted to collect views across age ranges (parents of younger children, teenagers and adult patients with CHD) and from those with complex and less complex CHD. Questions were developed by the authors and the content and language revised based on feedback from the charity representatives and PPI group.…”
Section: Participants and Data Collectionmentioning
confidence: 99%
“…The Children's Heart Federation, Little Hearts Matter and the Somerville Foundation, all of which are national UK charities dedicated to the support of patients with CHD and their families, facilitated and moderated one or more closed, anonymous, asynchronous online discussion groups via their Facebook pages, following an approach that we have successfully used in previous work. 19 20 We specifically chose these three charities because we wanted to collect views across age ranges (parents of younger children, teenagers and adult patients with CHD) and from those with complex and less complex CHD. Questions were developed by the authors and the content and language revised based on feedback from the charity representatives and PPI group.…”
Section: Participants and Data Collectionmentioning
confidence: 99%
“…10 Our qualitative research showed that clinicians and parents hold differing views about which specific postoperative events should be counted as adverse early outcomes of pediatric cardiac surgery. 11,12, Therefore, we used the term morbidity, a state of health generally viewed as bad for you, to label the range of adverse early outcomes (excluding death). We recognized that not all such adverse early outcomes are directly caused by the surgical procedure, although they do arise as a direct consequence of children undergoing cardiac surgery.…”
mentioning
confidence: 99%
“…We believe that these data and analyses can help surgeons, because the degree of PFC can be preliminarily assessed with preoperative computerized tomography [ 17 ]. This preliminary assessment can be used to inform the the surgeon’s preoperative decision regarding which surgical to use and the surgeon’s communication with the patient’s family, informing them of the possible postoperative complications, which constitute an important part of preoperative conversations with family members [ 30 ].…”
Section: Discussionmentioning
confidence: 99%